ANALISIS TINGKAT KEPUASAN KONSUMEN TERHADAP PELAYANAN WARUNK BENDITO DI KAWASAN MEGAMAS MANADO - Mulyadi ., Buton; Rine ., Kaunang; Sherly Gladys Jocom (AGRI-SOSIOEKONOMI, 2019)
This study aims to determine the level of customer satisfaction with Warunk Bendito service in the Megamas Manado area. This research was conducted in three months starting from preparation to compiling the research report from January 2019 to March 2019. This study uses primary and secondary data. The sampling method in this study was done by accidental sampling. Primary data collection is done by interview technique directly to 60 respondents based on questionnaires that have been prepared in advance. While secondary data collection is obtained from existing documents Warunk Bendito, books available at local bookstores and the internet through google scholar searches to access articles from various scientific journals and other university â€œskripsiâ€ related to this research, especially concerning consumer satisfaction with service. The results of the study using the Likert Scale analysis showed that the index of the level of consumer satisfaction with the service of Warunk Bendito in the Megamas area of Manado was at the point of 83.2% which was in the very satisfied category.*jnkd+erprm*